2008
DOI: 10.4103/0973-3930.43099
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of aspirin for adults with diabetes

Abstract: BACKGROUND:To evaluate the prescription of aspirin for primary and secondary prevention of cardiovascular disorders in diabetic patients, in the light of American Diabetes Association guidelines.MATERIALS AND METHODS:In this retrospective analysis, presence of any cardiovascular disease or cardiovascular disease risk factor as defined in American Diabetes Association guidelines and the use of aspirin and other medication data were extracted from the case files of 100 patients with type 2 diabetes mellitus visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…This was similar to previous studies that reported both types of medications were commonly omitted in elderly patients. 7,9,11,20,21 The prevalence of under-prescription of aspirin for primary prevention of CVD, which was the most common omitted medication in elderly type 2 diabetic patients in this study, was close to a previous study by Sabitha et al 22 The reason may be because that article used the criteria for under-prescription based on the Thai diabetes guideline of 2014. For the use of aspirin, the guideline gives a moderate recommendation based on evidence from previous studies that showed the benefit of aspirin in the primary prevention of CVD.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This was similar to previous studies that reported both types of medications were commonly omitted in elderly patients. 7,9,11,20,21 The prevalence of under-prescription of aspirin for primary prevention of CVD, which was the most common omitted medication in elderly type 2 diabetic patients in this study, was close to a previous study by Sabitha et al 22 The reason may be because that article used the criteria for under-prescription based on the Thai diabetes guideline of 2014. For the use of aspirin, the guideline gives a moderate recommendation based on evidence from previous studies that showed the benefit of aspirin in the primary prevention of CVD.…”
Section: Discussionsupporting
confidence: 81%
“…This result was consistent with the low prevalence of under-prescription of aspirin and statins for secondary prevention of cardiovascular events in this study which was similar with a previous study. 22 The strength of this study is that it is one of the few studies on under-prescription in elderly type 2 diabetic patients. The results can bring improvements in the quality in the care of diabetic patients in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of previous antiplatelet use before the current stroke attack among diabetic patients was 38.3%, with most (69.9%) on aspirin as monotherapy. This prevalence was lower than that reported in some studies that included all diabetic patients from the US (54%), the UK (52%), India (100%), and in diabetic patients with cardiovascular disease from Palestine (56.9%) [12,13,14,24].…”
Section: Discussionmentioning
confidence: 57%
“…This result is higher when compared to the study conducted in Saudi Arabia, of 312 patients, aspirin was indicated for 17.0% but it was not prescribed; it was both indicated and prescribed in 36.2% of the cases [1]. When compared to the study conducted in India [21], 11% of patients were prescribed with an indication for a primary prevention which is similar with this study, 10.6%; however, 10% of the patients were not utilized despite indicated for a primary prevention which is higher than this study (3.6%) and there was no documentation for the reasons not using aspirin while this study found that 55.2% of patients were reasoned “not prescribed” .…”
Section: Discussionmentioning
confidence: 80%